ANALISIS PENGARUH MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI KANTOR PELAYANAN PAJAK BUMI DAN BANGUNAN KOTA PALEMBANG - Yasmina Martini (Fakultas Ekonomi Universitas Tridinanti Palembang, 2013)
Ã‚Â ABSTRACTÃ‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â This research aims to know the influence analysis of motivationÃ‚Â and Leadership sytle on employees work productivity (Y) at construction and tax office in Palembang city.Ã‚Â The are three hypothesis were evaluated in this research. First, the significant influence among motivation with employees work productivity. Second, the significant influence among leadership style with employees work productivity. Third, the significant influence among motivation and leadership style together with employees work productivity.This research population take in all employees at Construction and tax office in Palembang City which whole 54 employees, and sample totally 54 employees use population technique no sampling.This instrument of collecting data use questionare which use scale likert were assembled based on construct that armful from theories, and applied on operation variable. To know the validity of instrument, the wvaluation of validity is done, with face validity characteristic.Analysis result of research stated in 5% significant found (1) correlation coefficient among motivation with employees work productivity about 0.337 with regression equation Y = 29.010 + 0.660 X1 and determination coefficient about 0.113, (2) correlation coefficient among leadership style with employees work productivity about 0.642 with regression equation Y = 41.261 + 0.762 X2 and determination coefficient about 0.413, (3) correficient among motivation and leadership style together with employees work productivity about 0.676 with regression equation Y = 4.757 + 0.424 X1 + 0.711 X2 and determination coefficent about 0.457.Contribution that given both two independent variables to employees work productivity each about 11.3% and 41.3% without controlling the influence of one to the others, but together have influence about 45.7%.Based on the research which has has done at construction and tax office in Palembang city about the influence analysis of motivation and leadership style on employees work productivity has significant influence.Ã‚Â Keywords : Motivation, Leadership Style, Productivity.Ã‚Â